THE DIVERSITY AND ABUNDANCE OF GROUND HERBS IN LOWLAND MIXED DIPTEROCARP FOREST AND HEATH FOREST IN BRUNEI DARUSSALAM - Nurul Hazlina Zaini; Rahayu Sukmaria Sukri (BRIN Publishing (Penerbit BRIN), 2014)
ZAINI, N. H. & SUKRI, R. S. 2014. The diversity and abundance of ground herbs in lowland mixed dipterocarp forest and heath forest in Brunei Darussalam. Reinwardtia 14(1): 73 – 78. ?Herbaceous plants are important components of total plant species richness in tropical forests. Ground herb diversity and abundance were studied in a lowland Mixed Dipterocarp forest (Andulau) and a heath forest (Bukit Sawat) in Brunei Darussalam, Borneo. At each site, all ground herbs in twenty randomly selected 10 x 10 m subplots within a one hectare permanent plot were censused and identified. The study recorded a total of 20 families and 32 genera of ground herbs, with the family Zingiberaceae as the most abundant at both sites. Thirteen genera were recorded only at Andulau and 7 genera were exclusive to Bukit Sawat, with twelve genera common to both sites. Ground herb species richness appear higher at Andulau than Bukit Sawat (37 vs. 29), but this difference was not statistically significant at the subplot level. However, ground herb abundance and density were significantly higher at Bukit Sawat than Andulau (n = 846 vs. 385; 4230 vs. 1925 individuals ha-1). The more open canopy at Bukit Sawat may provide higher light availability here than at Andulau, which is characterised by a closed canopy. We suggest that light availability is the most important environmental factor influencing ground herb density and abundance at these sites.